Percutaneous removal of a precariously placed pericardial peripherally inserted central catheter. Issue 6 (November 2019) - Tyner, Trevor; McNaught, Noelle; Shall, Matthew B.; Lessne, Mark L.
Peripherally inserted central catheters provide access to the central chest veins and allow administration of long-term antibiotics, chemotherapy, blood products, fluids, and parenteral nutrition. Peripherally inserted central catheters provide an essential function and are routinely placed safely, but are not without risks. This case describes an unusual complication of peripherally inserted central catheter perforation into the pericardial space with subsequent successful percutaneous removal.